PENGARUH PENYULUHAN KESEHATAN TENTANG ANEMIA MENGGUNAKAN MEDIA VIDEO TERHADAP PENGETAHUAN REMAJA PUTRI DI SMA NEGERI 6 PONTIANAK (Al-Insyirah Midwifery: Jurnal Ilmu Kebidanan (Journal of Midwifery Sciences), 2025)
Adolescent girls have a rate of anemia quantified by the World Health Organization with 29.6% Adolescent anemia involved children associated with poor physical growth, in delayed age of first menarche (first period) and the immune status is reduce but not crack down. The academic performance. If they become anemic, it could decrease movement, thought, and emotional behavior because iron is involved in many functions that adolescent girls need to optimize. Furthermore, decreases these parameters cannot be good for school. Femininity Adolescence Cancelation of Funding Announcement in full because video is multisensorial, it tells the easy and makes up to create a good media stimulation signal. The aim of the present research is to investigate scholar training and qualification enhancement of adolescent girls about anemia through video media increases their knowledge at SMA Negeri 6 Pontianak. This investigation utilizes a quantitative approach that employs a pre-experimental design. The population studied had a total of 178 female students, the sample size was 45 students chosen by purpose. The instruments employed for research were a video and a questionnaire that comprised 15 questions. The knowledge of adolescent girls increased from 77.18 to 87.99 following the delivery of health-related videos via media. The Wilcoxon test's results were less than 0.05, specifically 0.000. Conclusion There is a significant benefit to health education about anemia  via video media that increases the knowledge of adolescent girls at the sixth grade of SMAN 6 Pontianak.
Keywords: Anemia; Knowledge; Health Education; Young Women; Videos